2018
DOI: 10.1088/1674-1056/27/7/077405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn substitution on superconductivity in iron selenide (Li, Fe)OHFeSe single crystals

Abstract: As an essential component of the Materials Genome Initiative aiming to shorten the period of materials research and development, combinatorial synthesis and rapid characterization technologies have been playing a more and more important role in exploring new materials and comprehensively understanding materials properties. In this review, we discuss the advantages of high-throughput experimental techniques in researches on superconductors. The evolution of combinatorial thin-film technology and several high-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
2
5
0
Order By: Relevance
“…Moreover, one typical EELS pattern of Mn doped films is shown in Figure 1(c). The presence of L3.2 edges for Mn and Fe indicates that Mn ions are incorporated into the lattice of FeSe-11111 films, not left as impurities, which is consistent with the case of Mn-doped FeSe-11111 single crystals [21]. Because of the small difference in ionic sizes for Mn and Fe, it is expected that the incorporated Mn ions substitute for Fe ions at the crystallographic tetrahedral sites.…”
Section: Characterization Of Crystal Structure and Elemental Mnsupporting
confidence: 75%
“…Moreover, one typical EELS pattern of Mn doped films is shown in Figure 1(c). The presence of L3.2 edges for Mn and Fe indicates that Mn ions are incorporated into the lattice of FeSe-11111 films, not left as impurities, which is consistent with the case of Mn-doped FeSe-11111 single crystals [21]. Because of the small difference in ionic sizes for Mn and Fe, it is expected that the incorporated Mn ions substitute for Fe ions at the crystallographic tetrahedral sites.…”
Section: Characterization Of Crystal Structure and Elemental Mnsupporting
confidence: 75%
“…After synthesis, we needed to determine the precise composition and crystallographic occupancy of all dopants. There has been multiple works to date on similar transition metal doping in the (LiOH)FeSe system, but none have been able to quantify the crystallographic location of the transition metal dopant [50][51][52][53] . The location of the transition metal dopant is incredibly important in the realization of different physical properties as superconductivity in the iron chalcogenide sys-tems is very sensitive to doping 4,49,54 .…”
Section: Hydrothermal Synthesis and Crystallographic Resultsmentioning
confidence: 99%
“…It is worth mentioning that the present results of the films are different from the previous observations of TMdoped (Li,Fe)OHFeSe single crystals obtained by a hydrothermal ion-exchange method, [5] in which the TM doping into the FeSe layers has been reported. [26,27,36] A possible reason for that is the more limited lattice tolerance of the epitaxial films than the single crystals, due to the presence of substrate in the film growth.…”
Section: Methodsmentioning
confidence: 99%
“…Previous results have shown that the Mn doping can affect the superconducting critical temperature (T c ) to certain extent in the (Li,Fe)OHFeSe single crystals. [26][27][28] It is desirable to further study the interplay between the interlayer doping of various TMs and the superconductivity in the (Li,Fe)OHFeSe system.…”
Section: Introductionmentioning
confidence: 99%